2014
DOI: 10.1080/03081087.2014.952729
|View full text |Cite
|
Sign up to set email alerts
|

When is a Hamiltonian matrix the commutator of two skew-Hamiltonian matrices?

Abstract: The mapping Φ n (A, B) = AB − BA, where the matrices A, B ∈ C 2n×2n are skew-Hamiltonian with respect to transposition, is studied. Let C n be the range of Φ n : we give an implicit characterization of C n , obtaining results that find an application in algebraic geometry. Namely, they are used in [R. Abuaf and A. Boralevi, Orthogonal bundles and skew-Hamiltonian matrices, In Preparation] to study orthogonal vector bundles. We also give alternative and more explicit characterizations of C n for n ≤ 3. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The study of the varieties C r,n has led us to prove a somewhat curious result, that we have not been able to find anywhere in literature, and that we therefore report here. Similar results were recently obtained by [Nof13] using completely different techniques.…”
Section: Dominant Maps and Low-dimensional Casessupporting
confidence: 91%
See 2 more Smart Citations
“…The study of the varieties C r,n has led us to prove a somewhat curious result, that we have not been able to find anywhere in literature, and that we therefore report here. Similar results were recently obtained by [Nof13] using completely different techniques.…”
Section: Dominant Maps and Low-dimensional Casessupporting
confidence: 91%
“…Even more interesting would be finding out whether the map φ composed with the projection P(S 2 V ) ։ P(S 2 V ≤r ) is surjective for some value of the rank r. In other words, is there an r for which all symmetric matrices of rank r are of the form AJB − BJA for a pair of skew-symmetric matrices (A, B)? Noferini [Nof13] has shown that the statement is false for r = 2, any n. The question remains open for higher values of r.…”
Section: Dominant Maps and Low-dimensional Casesmentioning
confidence: 98%
See 1 more Smart Citation